Evaluating the treatment effectiveness and efficiency of Carriere Distalizer: a cephalometric and study model comparison of Class II appliances - Kaifeng Yin; Eugene Han; Jing Guo; Toshihiko Yasumura; Dan Grauer; Glenn Sameshima (SpringerOpen, 2019)
Abstract Background The purpose of this study was to evaluate the treatment effectiveness of Carriere Distalizer in comparison to Class II intermaxillary elastics and Forsus. Methods Three groups of patients treated with Class II intermaxillary elastics (n = 18), Carriere Distalizer (n = 18), and Forsus appliance (n = 18) were collected from three private orthodontic practices. Inclusion criteria were as follows: (1) 10-14 years old of start age with permanent dentition, (2) no history of previous orthodontic treatment, (3) complete pre- and post-treatment records, (4) dental Class II division 1 (end-to-end or more), (5) no pre-treatment transverse discrepancy, (6) non-extraction treatment plan, and (7) Class I post-treatment occlusal relationship. The data consisted of cephalometric and study model measurements from pre- and post-treatment records and treatment time. Two-tail Student t test was used to analyze the differences in cephalometric changes and dental corrections between Carriere Distalizer group and Class II elastics/Forsus group. Results All three groups of patients showed no differences in the age of treatment initiation, pre-treatment cephalometric measurements and discrepancy index (DI). The time of Class II correction for Carriere Distalizer was significantly shorter than that for Class II elastics; there was no difference in the length of Class II correction between Carriere Distalizer and Forsus groups. The amount of Class II correction (canine/molar relationship) was significantly lower for Carriere Distalizer when compared with Forsus appliance. Carriere Distalizer, similarly to Class II elastics, did not induce any statistically significant correction in skeletal component (ANB and Wits appraisal). Conclusions There is no clinically significant skeletal correction induced by Carriere Distalizer in growing patients. Carriere Distalizer can be applied to treatment of mild to moderate Class II dental malocclusion over 6 months on average, although the total treatment time may be prolonged due to various side effects. Overall, the Carriere Distalizer appears to be no more effective or efficient than alternatives in the treatment of Class II malocclusion.